Comparative SELDI-TOF-MS profiling of low-molecular-mass proteins from Lignosus rhinocerus (Cooke) Ryvarden grown under stirred and static conditions of liquid fermentation. - Lau, B.F.; Aminudin, N.; Abdullah, N. (Elsevier, 2011)
Mushrooms are considered as important source of biologically active compounds which include low-molecular-mass protein/peptides (LMMP). In this study, we attempted to profile the LMMP from Lignosus rhinocerus, a wild medicinal mushroom, grown by static cultures (SC) and in stirred tank reactor (STR). Crude water extract (CWE) and protein fractions were profiled using H50 ProteinChip® arrays and SELDI-TOF-MS. Three protein peaks of 5.8, 6.9 and 9.1kDa were found to be common to spectra of L. rhinocerus CWE from both culture conditions. Partial protein purification has resulted in detection of more peaks in the spectra of protein fractions. For protein fractions of L. rhinocerus cultured in STR, most peaks were observed in the range of 3-8kDa whereas some peaks with molecular mass up to 14.3kDa were noted in spectra of protein fractions from SC. Our results have demonstrated the optimization of profiling method using SELDI-TOF-MS for fungal LMMP.